8x+5y=9 3x+2y=4 ( by substitution method )
Answers
Answered by
36
Hi...☺️
Here is your answer...✌️
8x + 5y = 9 -----(1)
3x + 2y = 4 -----(2)
From (1) , we have
8x + 5y = 9
8x = 9 - 5y
x = (9 - 5y)/8 -----(3)
Putting value of x in eq (2) , we get
![\frac{3(9 - 5y)}{8} + 2y = 4 \\ \\ \frac{27 - 15y + 16y}{8} = 4 \\ \\ 27 + y = 4 \times 8 \\ \\ y = 32 - 27 \\ \\ \implies y = 5 \frac{3(9 - 5y)}{8} + 2y = 4 \\ \\ \frac{27 - 15y + 16y}{8} = 4 \\ \\ 27 + y = 4 \times 8 \\ \\ y = 32 - 27 \\ \\ \implies y = 5](https://tex.z-dn.net/?f=+%5Cfrac%7B3%289+-+5y%29%7D%7B8%7D+%2B+2y+%3D+4+%5C%5C+%5C%5C+%5Cfrac%7B27+-+15y+%2B+16y%7D%7B8%7D+%3D+4+%5C%5C+%5C%5C+27+%2B+y+%3D+4+%5Ctimes+8+%5C%5C+%5C%5C+y+%3D+32+-+27+%5C%5C+%5C%5C+%5Cimplies+y+%3D+5)
Putting y = 5 in eq (3) , we get
![x = \frac{9 - 5 \times 5}{8} \\ \\ x = \frac{9 - 25}{8} = \frac{ - 16}{8} \\ \\ \implies x = - 2 x = \frac{9 - 5 \times 5}{8} \\ \\ x = \frac{9 - 25}{8} = \frac{ - 16}{8} \\ \\ \implies x = - 2](https://tex.z-dn.net/?f=x+%3D+%5Cfrac%7B9+-+5+%5Ctimes+5%7D%7B8%7D+%5C%5C+%5C%5C+x+%3D+%5Cfrac%7B9+-+25%7D%7B8%7D+%3D+%5Cfrac%7B+-+16%7D%7B8%7D+%5C%5C+%5C%5C+%5Cimplies+x+%3D+-+2)
HENCE,
x = -2 , y = 5
Here is your answer...✌️
8x + 5y = 9 -----(1)
3x + 2y = 4 -----(2)
From (1) , we have
8x + 5y = 9
8x = 9 - 5y
x = (9 - 5y)/8 -----(3)
Putting value of x in eq (2) , we get
Putting y = 5 in eq (3) , we get
HENCE,
x = -2 , y = 5
Answered by
25
Hiii friend,
8X +5Y = 9.........(1)
3X +2Y = 4........(2)
FROM EQUATION 1 WE GET,
8X +5Y = 9
8X = 9-5Y
X = 9-5Y/8........(3)
PUTTING THE VALUE OF X IN EQUATION (2)
3X +2Y = 4
3 × (9-5Y/8) +2Y = 4
27 - 15Y /8 +2Y = 4
27-15Y +16Y = 4×8
Y = 32-27
Y = 5
Putting the value of Y in equation (3)
X = 9-5Y/8 = 9 - 5 × 5 /8 = -16/8 = -2
Hence,
X = -2 and Y = 5
HOPE IT WILL HELP YOU...... :-)
8X +5Y = 9.........(1)
3X +2Y = 4........(2)
FROM EQUATION 1 WE GET,
8X +5Y = 9
8X = 9-5Y
X = 9-5Y/8........(3)
PUTTING THE VALUE OF X IN EQUATION (2)
3X +2Y = 4
3 × (9-5Y/8) +2Y = 4
27 - 15Y /8 +2Y = 4
27-15Y +16Y = 4×8
Y = 32-27
Y = 5
Putting the value of Y in equation (3)
X = 9-5Y/8 = 9 - 5 × 5 /8 = -16/8 = -2
Hence,
X = -2 and Y = 5
HOPE IT WILL HELP YOU...... :-)
Similar questions